Phylogenetic relationships and comparative larval morphology of epigean and stygobitic species of Limbodessus Guignot, 1939 (Coleoptera: Dytiscidae: Bidessini), with a key of identification - Michat, Mariano C.; Alarie, Yves; Watts, Chris H. S. (Zootaxa, 2012)
The larvae of five epigean and 25 stygobitic species of the diving beetle genus Limbodessus Guignot, 1939 are describedand illustrated for the first time, with special emphasis on morphometry and chaetotaxy of the cephalic capsule, headappendages, legs, last abdominal segment and urogomphi. Those of the following five epigean species are described: L.amabilis (Clark, 1862), L. compactus (Clark, 1862), L. inornatus (Sharp, 1882), L. praelargus (Lea, 1899), L. shuckardii(Clark, 1862). The 25 stygobitic larvae described are: L. barwidgeeensis Watts & Humphreys, 2006, L. bigbellensis(Watts & Humphreys, 2000), L. challaensis (Watts & Humphreys, 2001), L. cooperi Watts & Humphreys, 2006, L.eberhardi (Watts & Humphreys, 1999), L. exilis Watts & Humphreys, 2006, L. fridaywellensis (Watts & Humphreys,2001), L. hillviewensis (Watts & Humphreys, 2004), L. hinkleri (Watts & Humphreys, 2000), L. leysi Watts & Humphreys,2006, L. macrohinkleri Watts & Humphreys, 2006, L. masonensis (Watts & Humphreys, 2001), L. millbilliensis Watts &Humphreys, 2006, L. mirandaae Watts & Humphreys, 2006, L. morgani (Watts & Humphreys, 2000), L. nambiensisWatts & Humphreys, 2006, L. ordinarius Watts & Humphreys, 2009, L. palmulaoides Watts & Humphreys, 2006, L.pulpa (Watts & Humphreys, 1999), L. raeae Watts & Humphreys, 2006, L. raesideensis (Watts & Humphreys, 2001), L.windarraensis (Watts & Humphreys, 1999), L. yandalensis Watts & Humphreys, 2006, L. yarrabubbaensis Watts & Humphreys, 2009, L. yuinmeryensis (Watts & Humphreys, 2003). The morphology and chaetotaxy of epigean vs.stygobitic species are compared, and a key for the identification of the species is presented. Contrary to their epigeancounterparts, larvae of stygobitic Limbodessus have turned out to be very divergent morphologically. In addition to thecommon characteristics associated with an underground living (i.e., absence of stemmata, reduced pigmentation, and thinor soft exoskeleton), larvae of these species have undergone a variable modification of the frontoclypeus and have evolvedrelatively shorter tarsal claws. Two morphological groups of stygobitic species are evident, one including species lessdeviated from the ancestral (epigean) condition and another group comprising more modified species that typically havea larger size, a more or less pyriform head with a digitiform nasale, and a strongly reduced occipital foramen. Primarychaetotaxy of the species has remained a very conservative expression of the phenotype. Secondary chaetotaxy showsvariation among the species, the most obvious being the variable number of lamellae clypeales and the presence or absenceof secondary setae on the urogomphus. The phylogenetic relationships of Limbodessus are analyzed cladistically. Larvaeof this genus lack the primary pore ABc, which is a synapomorphy of the tribe Bidessini. As presently defined, Limbodessus is probably paraphyletic with respect to Allodessus Guignot, 1953.